Differential Response of the Primate HPG Axis to N-Methyl-d, l-aspartate, but not to Kisspeptin Challenge under Euglycemic and Hypoglycemic Conditions - Wahab, F.; Zaman, W-uz.; Shahab, M. (Hormone and Metabolic Research, 2012)
Hypoglycemia inhibits the hypothalamic-pituitary-gonadal (HPG) axis by still incompletely deciphered mechanisms. Many evidences suggest that the hypoglycemia-induced inhibition of the HPG axis involves alteration of the hypothalamic gonadotropin-releasing hormone (GnRH) release, but neuroendocrine factors responsible for this alteration are yet to be completely elucidated. The current study was carried out to ascertain whether insulin-induced hypoglycemic suppression of the HPG axis involves modulation of responsiveness of the GnRH neuron to kisspeptin and excitatory amino acids (EAA) drives. Five intact chair-restraint habituated adult male rhesus monkeys (Macaca mulatta) were given intravenous boli of GnRH, hCG, human kisspeptin-10 (KP10), NMDA (N-methyl-d, l-aspartate, an EAA analogue), and vehicle in both insulin (1 IU/kg)-induced hypoglycemic (IIH) and normal euglycemic conditions. Specific RIAs were used for measuring plasma cortisol and T concentrations. KP10 and NMDA administration stimulated significantly (p<0.005) T secretion in both euglycemic and hypoglycemic monkeys. Mean post-KP10 T concentrations and AUC were comparable between euglycemic and hypoglycemic monkeys. However, mean post-NMDA T levels and AUC in hypoglycemic animals were significantly lower (p<0.01–0.005) as compared to the corresponding values in euglycemic animals. T response to GnRH and hCG was similar between hypoglycemic and euglycemic monkeys. Vehicle did not affect plasma T concentrations in all conditions. Our results demonstrate that while the primate HPG axis response to kisspeptin stimulation remains intact that to EAA excitation is attenuated in hypoglycemic conditions, suggesting that hypogonadism in IIH is contributed, in part, by reduced sensitivity of the GnRH neurons to EAA signaling in the primate hypothalamus.
Keywords: hypoglycemia; kisspeptin; GPR54; NMDA; EAA; GnRH; testosterone